More and better jobs: conceptual framework and monitoring indicators of quality of work and employment in the EU policy arena - RECWOWE; Peña-Casas, Ramón (Edinburgh, 2009)
"In the framework of the so-called Lisbon Strategy introduced in 2000 the European Union has put the synergy between quality and quantity of jobs in an overarching position as a mean to achieve the ambitious collective goal of becoming the most competitive knowledge economy capable of creating not only more but better jobs. In this chapter we will review how the issue of quality in work and employment has been introduced in European policy arena through the European Employment Strategy (EES) (section 1) and the related conceptual framework and monitoring indicators (section 2). We will discuss some of the results issued from the research on quality in work and employment in Europe (section 3). Although economic literature and the European rhetoric appear unclear about the real effectiveness of the virtuous synergy between quality and quantity of jobs we show that empirical findings suggest that relationship between both is nevertheless better apprehended in terms of synergies rather than in terms of supposed tensions or negative trade-offs."